Pucuk Bang, A Balinese Musical Composition Komposisi | Pucuk Bang, Sebuah Komposisi Karawitan Bali - Dwiki Yunadika; I Ketut Muryana (GHURNITA: Jurnal Seni Karawitan, 2021)
Bang bang flowers are still needed for religious ceremonies. As long as Hinduism is still firmly established in Bali, the bud flower will still be needed. Not only fulfilling the need for ceremonial facilities, shoots also have a special value, which we should protect and preserve their existence. Pucuk bang is the title of this creative percussion work, which uses the media to express gamelan gong kebyar. This work was inspired by seeing shoots of bang flower plants in the yard of the house. From the etymological meaning of the bud flower, this shoot was created. The method used in this work is the method proposed by Alma M. Hawkins, in the creation of dance, namely the Assessment Stage (exploration), Experiment Stage (improvisation), and Forming Stage. The concept of this work is guided by the Tri Angga concept (kawitan, pengwak, pengcet) and still uses traditional patterns. These traditional patterns were developed from the structure of the song, the technique of the game/game motif with the arrangement of musical elements such as: tone, melody, rhythm, tempo, harmony and dynamics. This creative percussion entitled shoot bang has a duration of 11 minutes and 12 seconds using 28 supporters including the stylist. This percussion creation by shoot bang was presented in a concert, which was recorded at Green Kubu, Br. Sebunibus, Nusa Penida.